BIOETHICS AS A FACTOR OF INTEGRATION OF PHYSICIANS AND PATIENTS FROM DIFFERENT COUNTRIES AND FAITHS - E. P. Mikhalovska-Karlova (Эпилепсия и пароксизмальные состояния, 2016)
Bioethics is examined through the context of the technological advancement of civilization. It has been shown that the most serious technological achievements are tied to the science of the brain. This science requires the use of bioethics, whose principles and norms are called to help medicine preserve the health, quality of life, and life of a human. For this to be possible, it is crucial for not only doctors, but also patients from different countries and of different nationalities and faiths to combine forces. The founders of ILAE understood this not long before the appearance of the field of bioethics in the beginning of the 20th century. This was not a coincidence: epilepsy is found to be a model for the study of the structural and functional organization of the brain. The tradition of ethics in Russian neurology was started by the father of Russian neuroscience, V.M. Bekhterev, who established RLAE only 4 months after the organization of ILAE. Today, RLAE and the All-Russian Society of Neurologists continue to develop this tradition. Only through combined forces is it possible to achieve a full implementation of the ethical mechanism of control in medicine.